When Faith Becomes Coping: Gambaran Strategi Religius Remaja dalam Menghadapi Tekanan Kehidupan - A. As'ad Fathan; Henny Indreswari; Khairul Bariyyah; Muslihati; Yuliati Hotifah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2026)
Adolescents are in a developmental phase that is vulnerable to academic, social, emotional, and spiritual pressures. In dealing with these pressures, religious coping can serve as an adaptive strategy that helps students find meaning, gain calmness, and build spiritual support. This study aims to describe the level of religious coping among students of SMPN 1 Bontonompo Selatan based on age, gender, grade level, and participation in religious organizations. This research employed a quantitative approach with a descriptive design. The sample consisted of 90 students aged 12–15 years selected using purposive sampling. The instrument used was a religious coping scale adapted from Savira et al. and based on Pargament’s theory of religious coping. The data were analyzed descriptively using JASP. The results showed that students’ religious coping was generally in the moderate category, with a percentage of 63.3%. Based on students’ characteristics, religious coping showed variations, although most students remained in the moderate category. Students who participated in religious organizations had a higher proportion in the high category than those who did not. In addition, positive religious coping had a higher mean score than negative religious coping. These findings indicate that students have begun to use religious values as a strategy for dealing with pressure, but they still need reinforcement through guidance and counseling services based on religious values.